2016
DOI: 10.1021/acs.iecr.5b04730
|View full text |Cite
|
Sign up to set email alerts
|

CoMoNi Catalyst Texture and Surface Properties in Heavy Oil Processing. Part I: Hierarchical Macro/Mesoporous Alumina Support

Abstract: A pair of mesoporous and hierarchical macro/mesoporous alumina-supported catalysts having distinct textural parameters have been chosen to elucidate the effect of texture on activity in hydrodesulfurization (HDS) and hydrodemetallization (HDM) of heavy tatar oil possessing extremely high viscosity and sulfur content. For monitoring catalyst properties, the samples have been investigated by XRD, XFS, XPS, EXAFS, SEM, TEM, FTIR, TPD-NH3, mercury porosimetry, and N2 adsorption methods. Among different factors suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…Over the past decades, researchers have made tremendous experimental efforts to study the effects of hydrotreating catalyst structures, including pore distribution, pellet size, type, and textural properties of a catalyst carrier . Recently, hierarchical alumnia-supported catalysts with meso/macropores were reported to be used in heavy oil processing. , A hierarchical catalyst usually has two or more distinct pore size distribution peaks. As a result, it is not suitable to determine its restricted diffusion properties with the ratio of the molecule size to the average pore size because of the significantly complicated pore structure of this catalyst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past decades, researchers have made tremendous experimental efforts to study the effects of hydrotreating catalyst structures, including pore distribution, pellet size, type, and textural properties of a catalyst carrier . Recently, hierarchical alumnia-supported catalysts with meso/macropores were reported to be used in heavy oil processing. , A hierarchical catalyst usually has two or more distinct pore size distribution peaks. As a result, it is not suitable to determine its restricted diffusion properties with the ratio of the molecule size to the average pore size because of the significantly complicated pore structure of this catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…18 Recently, hierarchical alumnia-supported catalysts with meso/ macropores were reported to be used in heavy oil processing. 19,20 A hierarchical catalyst usually has two or more distinct pore size distribution peaks. As a result, it is not suitable to determine its restricted diffusion properties with the ratio of the molecule size to the average pore size because of the significantly complicated pore structure of this catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…A strategy to alleviate the intraparticle diffusion limitations by tailoring the pore structure has been proposed. Two representative experimental studies showed that the alumina-supported catalyst with a bimodal pore size distribution of 9 and 100 nm shows higher HDM activity than the catalyst with purely a mesopore diameter of 8 nm, and the hierarchically structured HDM catalyst with the most probable macropore diameter of 120 nm exhibits better HDM performance than that with 200 nm . A large amount of theoretical studies based on mathematical modeling of the diffusion behavior and reaction in the HDM catalysts has been conducted for in-depth analysis of the effects of the pore structure parameters. ,, Rao and Coppens optimized the broad pore network of a hierarchically structured HDM catalyst on the basis of the Random Spheres Model (RSM) with the optimization objective of the reaction rate of a single catalyst pellet at the pellet scale.…”
Section: Introductionmentioning
confidence: 99%
“…The catalysts usually employed for crude oil hydrotreatment conventionally include alumina-supported Mo sulfide promoted by Co and/or Ni [8][9][10][11][12][13][14][15]. In the case of medium and heavy oil hydroprocessing, mixed or multiple beds of catalysts are generally used to achieve better quality of the product.…”
mentioning
confidence: 99%
“…The catalyst performance increases as far as the feed is being supplied through the multiple layer or the multiple bed [16,18]. Studies have shown that noble metal-based catalysts (Pt and Pd) supported on alumina, used in hydrogenation reactions, despite having good catalytic performance in relation to the reactions of HDT, deactivate quickly by the adsorption of sulfur species present in industrial loads [10][11][12][13][14][15]. Some progress was achieved with the use of bimetallic catalysts with these two precious metals.…”
mentioning
confidence: 99%